Characterization of the Reaction Product of Se4N3Cl and Phenyl Hydrazine by 1H NMR - Dixit, Harish; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
Se4N3Cl was mixed with phenyl hydrazine in equimolar ratio and refluxed in non-polar solvent. The product formed was analyzed quantitatively, as well as mass, IR, electronic and 1H NMR spectrometrically and assigned as (Se4N3)2––N––NH––C6H5.